Geographic origin and host’s phylogeny are predictors of the gut mucosal microbiota diversity and composition in Mediterranean scorpionfishes (Scorpaena spp.) - Lilli, Ginevra; Sirot, Charlotte; Campbell, Hayley; Brophy, Deirdre; Graham, Conor T.; George, Isabelle F. (Frontiers in Marine Science, 2023)
The gut microbiome holds an important role in the health and homeostasis of fishes. However, despite the large diversity and distribution of this vertebrate group, only the intestinal microbiome of a limited number of freshwater and marine fish species has been well characterized to date. In this study, we characterize the gut mucosal microbial communities of three commercially valuable Scorpaena spp. (n=125) by using a comprehensive comparative dataset including 16S rRNA gene amplicon data from four different locations in the Mediterranean Sea. We report that the geographical origin of the individuals influences the diversity and the composition of the gut microbial communities more than the host’s phylogenetic relatedness in this fish group. Moreover, we observe a positive correlation between the composition of the gut microbiota and the phylogenetic distance between the hosts (i.e. phylosymbiosis). Finally, the core microbiota of each species is described both regionally and across the Mediterranean Sea. Only a few bacterial genera appear to be residents of the scorpionfishes’ gut microbiota across the Mediterranean Sea: Photobacterium, Enterovibrio, Vibrio, Shewanella, Epulopiscium, Clostridium sensu stricto 1 and Rombutsia in S. notata, Clostridium sensu stricto 1, Cetobacterium and Rombutsia in S. porcus, and only Clostridium sensu stricto 1 in S. scrofa. This study highlights the importance of investigating the gut microbiome across a species’ geographical range and it suggests this as a general procedure to better characterize the gut microbial ecology of each fish species.